(untitled) (Asian Journal of Social Science Studies, 2018)
The purpose of the research paper was to trace the origin of chieftaincy among the Waala of the Upper West Region of Ghana as well as discuss the emergence of the Wa chieftaincy conflict. The Waala monarchy and the Wa Naa are the custodians of Waala customs and culture which provide transparent processes for the choice of a new Wa Naa and other leaders and for any conflicts arising thereof. Chieftaincy disputes tend to be overlooked by the authorities expected to resolve them; probably because they perceive such conflicts as tractable and not complex. There are provisions within Waala society and in the Kingdom for indigenous means of dispute resolution that have been relegated to the background. The origin of chieftaincy among the Waala has been traced while the perceived causes of the Wa chieftaincy conflict has been discussed. This research paper is part of my PhD thesis that was submitted to the university but has not been published.